Fungal Diversity and Enzyme Activity Associated with the Macroalgae, Agarum clathratum. Issue 1 (2nd January 2019) - Lee, Seobihn; Park, Myung Soo; Lee, Hanbyul; Kim, Jae-Jin; Eimes, John A.; Lim, Young Woon
Abstract: Agarum clathratum, a brown macroalgae species, has recently become a serious environmental problem on the coasts of Korea. In an effort to solve this problem, fungal diversity associated with decaying A. clathratum was investigated and related β-glucosidase and endoglucanase activities were described. A total of 233 fungal strains were isolated from A . clathratum at 15 sites and identified 89 species based on morphology and a multigene analysis using the internal transcribed spacer region (ITS) and protein-coding genes including actin ( act ), β-tubulin ( benA ), calmodulin ( CaM ), and translation elongation factor ( tef1 ). Acremonium, Corollospora, and Penicillium were the dominant genera, and Acremonium fuci and Corollospora gracilis were the dominant species. Fifty-one species exhibited cellulase activity, with A. fuci, Alfaria terrestris, Hypoxylon perforatum, P. madriti, and Pleosporales sp. Five showing the highest enzyme activities. Further enzyme quantification confirmed that these species had higher cellulase activity than P . crysogenum, a fungal species described in previous studies. This study lays the groundwork for bioremediation using fungi to remove decaying seaweed from populated areas and provides important background for potential industrial applications of environmentally friendly processes.